Genetic parameters of days open in Charolais cattle of Cuba - Espinosa, José L; González Peña, Dianelys; Palacios Espinoza, Alejandro; Ortega, Ricardo; Guillén, Ariel (Revista Colombiana de Ciencias Pecuarias, 2016)
there is little information in Cuba regarding the genetic components of the postpartum period in beef cattle. Objective: to compare estimates of genetic parameters of days open (DO) obtained with three models in Charolais cattle of Cuba. Methods: data from individual reproductive control of Charolais cattle from 17 herds in two Cuban companies were analyzed. The sample consisted of 16,891 calvings from 4,593 cows, daughters of 190 sires and 2,770 dams. Up to 10 parities per female between years 1981 and 2005 were considered. The WOMBAT program was used to estimate variance components. Three models were applied; an univariate model (UM) for each separate parity until the sixth calving; a repeatability model (RM) with all parities; and a random regression model (ARM) taking the number of calving as an independent variable. Results: the overall average for DO was 171 ± 93 days. The trend of the average value for DO in each calving was decreasing from the first to the tenth parity, with a seasonal performance around 155 days between the fourth and eighth calving. DO heritability estimated by UM was variable, with values of 0.03 for the first calving and 0.06 for the sixth. These variations cannot be observed with RM that estimated a heritability of 0.06. Values of 0.05 in the first calving until 0.07 in the tenth were estimated with ARM. Genetic correlations among DO for different parities were close to unity. Conclusions: changes of the estimated heritability for DO through the productive life of a female can be observed with ARM. The heritability estimates were low and did not differ from the results reported in other beef cattle breeds.